EAHP European Statements Survey 2018, focusing on Section 1: Introductory Statements and Governance, Section 3: Production and Compounding, and Section 4: Clinical Pharmacy Services. Issue 1 (2nd December 2019) - Amann, Steffen; Underhill, Jonathan; Horák, Petr; Batista, Aida; Miljkovic, Nenad; Gibbons, Nicholas
Abstract : Objectives: The 2018 EAHP European Statements Survey focused on sections 1, 3 and 4 of the European Statements of Hospital Pharmacy. Statistical data on the level of implementation and on the main barriers to implementation of the Statements were collected. A further aim was to identify barriers in general, such as lack of awareness. Methods: An online questionnaire was sent to all hospital pharmacies in EAHP member countries. Data were analysed at Keele University School of Pharmacy, UK. As with previous reports, the survey was divided into three sections: section A, asking general questions about the hospital pharmacy; Section B, addressing questions about the current activity of pharmacists around each statement from Sections 1, 3 and 4; and Section C, focusing on their ability to implement the statements. Results: 719 complete responses were obtained from a sample of 5164 hospital pharmacies, giving a response rate of 14% (719/5164). Section A results indicated that 45% (323/719) of responders worked in teaching hospitals, 79% (568/719) of hospital pharmacies had 10 or fewer pharmacists, and 48% (345/719) of hospital pharmacies served over 500 beds. Section B results found a high percentage of positive responses for activity in section 1 (introductory statements and governance) and section 3 (production and compounding). However, responses to questions in section 4 (clinical pharmacy services) were more variable, with 6 of the 15 questions being answered positively by less than half of respondents. The five questions that revealed the lowest implementation levels were then analysed in greater detail. These questions corresponded to Statements 4.4, 4.5, 4.8, 1.1, and 4.2, which need the greatest effort for implementation. The major identified barriers to implementation were 'lack of capacity' and that 'other health professionals in the hospital fulfil the tasks'. Conclusions: This survey provides useful information on the implementation status (and the barriers to, and drivers of implementation) of sections 1, 3 and 4 of the Statements. This will allow the EAHP to plan its implementation support programme for its members. To increase the quality of data, as well as the feedback to hospital pharmacies, the EAHP is planning to combine the survey with the self-assessment tool of the European Statements of Hospital Pharmacy.